Genetic polymorphism of the BoLA-DRB3 gene in Jersey crossbred and Ongole cattle revealed by PCR-RFLP - Aravindakshan, T V; Nainar, A M (The Indian Journal of Animal Sciences, 2012)
The genetic diversity of the bovine class II DRB3 locus was investigated by polymerase chain reaction (PCR) and restriction enzyme analysis. Genomic DNA samples were isolated from 33 Jersey crossbred and 15 Ongole animals. A 304 bp fragment of the bovine lymphocyte antigen (BoLA)-DRB3 gene was amplitled by PCR and the amplified product was separately digested with Bst YI, HaeIII and Rsaf enzymes. Digestion with Bst YI resulted in 2 restriction patterns which corresponded exactly to the Bst YI patterns previously described for cattle. Digestion with HaeIII resulted in 7 patterns of which 6 patterns were previously described for cattle. A new HaeIII pattern was observed in both breeds studied. The fragment analysis with Rsaf revealed 11 different patterns either in homozygous or in the heterozygous form. The high degree of polymorphism observed in this study suggests the possibility of using this technique in the identification of superior haplotypes for disease resistance and utilizing them in breeding programmes.